MENDETEKSI PERILAKU FRAUD LAPORAN KEUANGAN DENGAN THEORY OF PLANNED BEHAVIOR (STUDI EMPIRIS PADA INDUSTRI PERBANKAN) - Christina, Lienai; Kristanto, Septian Bayu (Widya Mandala Surabaya Catholic University, 2019)
This study aim to examine factors that determined the intention towards fraud in financial statements in banking industry. Based on UU Perbankan No. 10 tahun 1998, banking industry are perceived to be safeguarded from fraud occurrences. On the other side, this study intends to examine the relevance of the theory of planned behavior in measuring intention and behavior towards fraud. A total of 158 questionnaires were collected. Structural equation modelling was used to test the model. The Findings indicates that attitude, subjective norms, and perceived behavioral control are influenced intention to fraud financial statements with R2 value 0.92. Thus, intention influenced behavior with R2 value 0.89. This study proved that if respondents are favor of financial statements fraud, so their intention strongly committed to financial statements fraud. Therefore, more positive intention to commit fraud leads behavior in financial statement fraud.